Moringa oleifera leaf extract ameliorates early stages of diabetic nephropathy in streptozotocin-induced diabetic rats - Ruttiya Thongrung, Patchareewan Pannangpetch, Laddawan Senggunprai, Sakkarn Sangkhamanon, Kampeebhorn Boonloh, Panot Tangsucharit (Journal of Applied Pharmaceutical Science, 2023)
Diabetic nephropathy (DN) is a long-term complication of diabetes mellitus. The characteristic of early-stage DN is glomerular hyperfiltration that has been linked to renal fibrosis. In this study, we investigated the effect of Moringa oleifera leaf extract (MOE) on DN in streptozotocin (STZ)-induced DN rats. Rats were injected with 50 mg/kg STZ to establish the DN model. Four weeks after receiving an injection of STZ, DN rats were administered distilled water, MOE (100 or 200 mg/kg body weight/day), dapagliflozin (1 mg/kg body weight/day), or combinations of these for further 8 weeks. DN rats exhibited significantly increased blood glucose (504.00 ± 28.41 mg/dl), proteinuria (192.85 ± 41.23 mg/24 hour), albuminuria (6.68 ± 1.54 mg/24 hours), blood urea nitrogen (47.14 ± 5.18 mg/dl), and creatinine clearance (5.64 ± 0.35 ml/minute) (p < 0.05) together with significantly increased malondialdehyde and decreased superoxide dismutase and catalase (p < 0.05). Administration of MOE could significantly reduce the high blood glucose, impaired renal function, and oxidative stress parameters of DN rats (p < 0.05). Histological examination of kidneys showed a thickening of the glomerular basement membrane and an increase in the mesangial matrix; all of these pathological changes were improved by MOE administration. The mRNA expression of transforming growth factor-beta 1 (TGF-β1) and collagen type IV were significantly increased in the kidney tissue of DN rats but were significantly downregulated in MOE -treated rats (p < 0.05). MOE could alleviate DN plausibly due to its activities in reducing blood glucose, oxidative stress, and fibrosis formation by downregulating the expression of TGF-β1 and collagen type IV genes. MOE may be useful as an alternative or supplementary medicine for treatment of DN.